IMPLEMENTATION OF GENDER EQUALITY OBJECTIVES IN UKRAINE ON THE BASIS OF INTERNATIONAL LAW - Yelagin V. P., (Pressing Problems of Public Administration, 2021)
The question of gender equality is becoming increasingly more popular in Ukraine. The UN and international standards in the area of gender equality are still being implemented in Ukrainian legislation. This process addresses numerous problems, including the world financial/economic crisis from 2008, the 2014 ’Revolution of dignity’ in Ukraine, increasing the level of armed activity in Ukraine. The key activities to solve these problems in Ukraine include positive learning experiences from successful foreign countries in this sphere, learning experience about gender equality and aligning national standards of protection against gender-based violence. The development of government policy has changed to more gender equality orientated approaches. Ukraine has so far not been largely successful, although has made positive steps and does not have the worst record on these issues. Since the start of the 21st century, these gender equality issues started to become more important.Based on the comparative analysis of scientific publications, activities of governmental and non-governmental foreign and domestic state and public organizations, the following conclusions and proposals can be formulated that allow the introduction of effective public policy in Ukraine in the field of equal rights and opportunities for women and men in many spheres of public life.The issue of ensuring gender equality in all spheres of public life remains an urgent issue for the spread of democratic norms in Ukraine. Discrimination on the basis of gender does not contribute to the socio-economic development of the country and its approximation to international standards, which are accepted worldwide.